Embracing an embodied theology in the time of corona: Mimetic synchronisation with the theological rhythms and first responder stance of the apostle Paul during the time of famine - Joubert, Stephanus J. (HTS teologiese studies, 2020)
Apart from constantly grappling with issues such as the inspiration of the Bible, theologians are also keen observers of cultural and societal changes and shifts and their impact on the interpretation of the Bible. Postmodernism serves as a briefcase in point. However, theologians do not seem to be equally responsive to natural disasters such as the present global COVID-19 pandemic. Whilst the presence of the coronavirus is reshaping the nature of our planet and threatening the well-being of all of its inhabitants, the future of formal theology is also under threat. As a matter of ‘academic survival’, a so-called ‘ancient-future’ approach is urgently called for, one that entails a mimetic rereading of the theologians of the Bible who were the first responders during the times of pandemics and other calamities. The apostle Paul served as our example in this regard. A ‘preferential option for the poor’, inherent in his theology, directly influenced his organisation of, and personal involvement in, two impactful collections for the poor in Judea during the extended periods of famine and poverty. Using ‘mimetically synchronising’ with his theological rhythms, corresponding embodied responses of theologians during the corona pandemic could become a reality. Only then will there be hope for a vibrant new post-corona theology, a lived one at that!Contribution: The focus of this article represents an exegetical, historical and practical reflection, within a paradigm in which the intersection of religious studies and social sciences generates an interdisciplinary contested discourse. The article comprises exegesis of the Ancient Near Eastern scriptures and the Early Church, including studies in the field of early Christian literature and the New Testament.